Cessation behaviours among smokers of menthol and flavoured cigarettes following the implementation of the EU Tobacco Products Directive: findings from the EUREST-PLUS ITC Europe Surveys. (12th September 2020) - Zatoński, Mateusz; Herbeć, Aleksandra; Zatoński, Witold; Janik-Koncewicz, Kinga; Driezen, Pete; Demjén, Tibor; Fernández, Esteve; Fong, Geoffrey T; Quah, Anne C K; Kyriakos, Christina N; McNeill, Ann; Willemsen, Marc; et al.
Abstract: The European Tobacco Products Directive (TPD) introduced a ban on characterizing flavours in cigarettes (2016), including menthol (2020). The longitudinal data analysis of the EUREST-PLUS International Tobacco Control (ITC) Project Europe Surveys ( n  = 16 534; Wave 1 in 2016 and Wave 2 in 2018) found significant but small declines in the weighted prevalence of menthol (by 0.94%; P  = 0.041) and other flavoured cigarette use (by 1.32%; P  < 0.001) following the 2016 TPD. The declines tended to be driven primarily by the menthol and flavoured cigarette (MFC) smokers switching to unflavoured tobacco. Cigarette consumption declined between waves, but there were no statistically significant difference in decline between MFC and unflavoured tobacco smokers on smoking and cessation behaviours between the waves.